PRARANCANGAN PABRIK KARBON AKTIF DARI BAGGASE FLY ASH (BFA) DENGAN AKTIFASI KIMIA MENGGUNAKAN KOH KAPASITAS 2.500 TON/ TAHUN - , MAHFUDL SIDIQ M; , Chandra Wahyu Purnomo, S.T., M.E., M.Eng., D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Activated carbon is a compound which widely used by companies or factories, such as water treatment, gas purification, sugar industry, waste water treatment. In the world of industry, activated carbon is very needed because it can adsorb the smell, color, gas, and metals. Activated carbon industry have large opportunities to developed, given the need of activated carbon which is increasing every year. The plant is planned to operate for 330 days / year with a production capacity of 2,500 tons activated carbon / year. The main raw material required is baggase fly ash as much as 23486.98 tons / year and as much potassium hydroxide 50% 4132.82 tons / year. The method that used to activating carbon is chemical activation with potassium hydroxide as the activating agent. Stages of chemical activation process is as follows: (i) impregnation (soaking) BFA with 50% KOH solution in the mixing tank (M-02), (ii) activation in a rotary kiln (RK) at a temperature of 600-800 Â° C, (iii) KOH washing with water in a stirred tank (M-03), (iv) purification activated carbon products through a process of drying and screening. As a supporting facility, utility unit cooling water supply needs as much as 41184 tons / year, as many as 305.4 kVA electricity, compressed air as much as 15,840 m3/yr, and steam as 60683.75 tons / year. This plant will be built in Tangerang, West Java, with consideration of raw material oriented. Tangerang region close to the sugar industry which produces baggase fly ash, and close to the port that facilitate the procurement of raw material potassium hydroxide which was imported from China as well as the marketing of activated carbon products. Plant location close to the river Cisadane as source of water for utility units. Calculation of economic evaluation results of fixed capital required amounted to $ 7,898,908.38 + Rp26.638.763.849, 27, and working capital of $ 2,637,457.09 + Rp13.867.914.525, 02. At 100% production capacity, obtained ROI before tax amounted to 36.77%, ROI after tax of 18.38%. POT before tax of 2.03 years, POT after tax amounted to 3.37 years with a BEP of 40.86%, SDP was 18.94%, and 25.4% DCFRR. Based on consideration of the evaluation results, the activated carbon plant with a capacity of 2,500 tons / year is worth to be studied further.